The Strategic Implementation of the Langkawi Tourism Blueprint 2011-2015: A Case Study Approach - Sijabat, Ferdi Nazirun (2013)
Tourism industry is the source of promising economic benefit to the host country. So that tourism planning and development are acknowledged as a mean to spur countries economic, due to the ability of the sector to further double the job creation, country’s receipt, raising standard of living and upgrade the infrastructure. The objective of the study is to evaluate the progress of the Langkawi Tourism Blueprint 2011-2015 implementation, to describe the role of LADA, MPLBP and other agencies in order to achieve the main objectives of the blueprint, to assess the implementation of the blueprint’s initiatives and the impact on tourist arrival and local people, to identify the challenges and opportunities in implementation of the blueprint. This study applies case study analysis. The study found that the implementation of the blueprint’s initiatives results 77.27% percent on November 2012. The launch of the blueprint has also increased the number of tourist arrival into Langkawi 3 million. The role of LADA, MPLBP and other agencies play critical role to control and monitor the implementation of the blueprint together with other agencies. The implementation of the blueprint’s initiatives in Langkawi is going on the track to achieve the main objective.